ABC of Pediatric Surgical Imaging - Andronikou, Savvas; Alexander, Angus; Kilborn, Tracy; Millar, Alastair J. W.; Daneman, Alan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book has been designed to serve as a quick reference that will assist in decision making. The book is ordered alphabetically according to diagnoses. The intention is that the clinician consults the information on a suspected diagnosis, and then considers the listed surgical and radiological differential diagnoses. A total of 80 common diagnoses are covered. For each diagnosis, the left-hand page presents information relevant to the surgeon, while the right-hand page is designed for the radiologist. The information for the surgeon comprises clinical insights, including symptoms, warnings, controversies, other important facts, and the surgical differential diagnosis. The radiologist is provided with lists of the primary and follow-on investigations, the imaging findings, and helpful tips, as well as the radiological differential diagnosis. Informative supporting images are included for each diagnosis. The authors are all experts in their fields, with extensive practical experience.
Achalasia -- Adenoid Hypertrophy -- Adrenal Masses (Other than Neuroblastoma) -- Anorectal Malformation -- Appendicitis (Acute) -- Ascariasis (Worm Bolus Obstruction) -- Biliary Atresia -- Bochdaleck Hernia (Congenital Diaphragmetic Hernia/CDH) -- Branchial Cleft Anomalies -- Bronchogenic Cysts -- Choledochal Cyst -- Congenital Cystic Adenomatoid Malformation (CCAM) -- Congenital Lobar Emphysema (CLE) -- Crohn's Disease -- Cystic Hygroma (Lymphatic Malformation) -- Duodenal Atresia (Duodenal Stenosis, Web) -- Duplex Kidney -- Duplication Cyst (Enteric Cyst) -- Empyema -- Epididymo-Orchitis -- Foreign Body Aspiration -- Foreign Body Ingestion (Oesophageal FB) -- Gallstones -- Gastro-Oesophageal Reflux -- Hemangioma $1 (BInfantile Soft Tissue/Cutaneous (Strawberry Nevus) -- Hemangioma $1 (BLiver (Hemangioendothelioma) -- Hematometrocolpos (Hydrometrocolpos) -- Hepatoblastoma -- Hiatus Hernia -- Hirschsprung's Disease (Colonic Aganglionosis) -- Horseshoe Kidney -- Hydatid Cysts (Echinococcus Cyst) -- Hydronephrosis -- Hypertrophic Pyloric Obstruction (HPO) -- Ileal Atresia -- Inguinal Hernia -- Intussusception -- Jejunal Atresia -- Lung Abscess -- Lymphoma -- Malrotation and Volvulus -- Meckel's Diverticulum -- Meconium Ileus -- Meconium Peritonitis -- Meconium Plug, Functional Immaturity Syndrome (Small Left Colon Syndrome) -- Mesoblastic Nephroma -- Morgagni Hernia -- Multicystic Dysplastic Kidney (MCDK) -- Necrotizing Enterocolitis (NEC) -- Nephroblastomatosis -- Neuroblastoma -- Non-Accidental Injury (NAI) -- Oesophageal Atresia -- Oesophageal Caustic Stricture -- Ovarian Cyst -- Pancreatitis (Acute) -- Parotid Mass -- Pelviureteric Junction (PUJ) Obstruction -- Posterior Urethral Valve (PUV) -- Ranula (Plunging Ranula) -- Renal Calculi -- Renal Ectopia (Crossed Fused Ectopia/Pelvic Kidney) -- Retropharyngeal Abscess (Pre-vertebral abscess) -- Rhabdomyosarcoma -- Sacrococcygeal Teratoma -- Scrotal Mass (See Sects. Torsion Testis and Epidydimo-Orchitis for (3z(BAcute Scrotum(3y(B) -- Sequestration Pulmonary (Sequestrated Segment) -- Sternomastoid Pseudotumour (Fibromatosis Colli) -- Takayasu's Arteritis -- Thymic Mass/Cyst -- Thyroglossal Cyst -- Thyroid Neoplasm -- Tonsillar Abscess (Quinsy) -- Torsion Testis -- Trauma Abdomen -- Trauma Chest -- Tuberculosis of the Abdomen -- Urachal Abnormality (Patent Urachus/Urachal Cyst/Sinus/Diverticulum) -- Varicocoele -- Venous Malformations (Including Klippel Trenaunay Syndrome) -- Vesicoureteric Reflux (VUR) -- Wilm's Tumour (Nephroblastoma).s
Keywords: Medicine; Radiology, Medical; Pediatrics; Surgery; Medicine & Public Health; Imaging / Radiology; Pediatric Surgery; Pediatrics